Characterization and optimization of a novel vaccine for protection against Lyme borreliosis. Issue 44 (4th November 2015) - Comstedt, Pär; Hanner, Markus; Schüler, Wolfgang; Meinke, Andreas; Schlegl, Robert; Lundberg, Urban
Abstract: Lyme borreliosis (LB) is the most common vector-borne disease in the northern hemisphere and there is no vaccine available for disease prevention. The majority of LB cases in Europe are caused by four different Borrelia species expressing six different OspA serotypes, whereas in the US only one of these serotypes is present. Immunization with the outer surface protein A (OspA) can prevent infection and the C-terminal part of OspA is sufficient for protection against infection transmitted by Ixodes ticks. Here we show that the order of the stabilized monomeric OspA fragments making up the heterodimers in our LB vaccine does not influence the induced immunogenicity and protection. Using bioinformatics analysis (surface electrostatics), we have designed an improved version of an LB vaccine which has an increased immunogenicity for OspA serotype 3 and an optimized expression and purification profile. The OspA heterodimers were highly purified with low amounts of endotoxin, host cell proteins and host cell DNA. All three proteins were at least 85% triacylated which ensured high immunogenicity. The LB vaccine presented here was designed, produced and characterized to a level which warrants further development as a second generation human LB vaccine.